2018
DOI: 10.1002/pbc.27028
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Langerhans cell histiocytosis with a modified risk‐adapted protocol—experience from a tertiary cancer institute in India

Abstract: RO+LCH receiving oral etoposide augmented induction and maintenance had early and durable responses. Prolonging maintenance lowered reactivation rates in RO+ and RO-LCH, resulting in excellent survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…This study has given an overview of paediatric LCH in resource limited settings in a public sector hospital in Pakistan with 25% of children presenting at ages less than 2 years with male preponderance. In contrast to Narula et al 7 , who noticed median age of the patients as 36 months in their population. However male predominance was observed in their study group like our study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This study has given an overview of paediatric LCH in resource limited settings in a public sector hospital in Pakistan with 25% of children presenting at ages less than 2 years with male preponderance. In contrast to Narula et al 7 , who noticed median age of the patients as 36 months in their population. However male predominance was observed in their study group like our study.…”
Section: Discussionmentioning
confidence: 57%
“…11,12 In our study, among the children less than 2 years 38% achieved complete remission, 37% abandoned and 25% expired as demonstrated to be higher risk when presented at younger age.In the present study, only 49% of the total children had risk organ involvement with only one third able to complete treatment and rest were expired or abandoned treatment. In contrast,Narula et al 7 showed few cases with RO+ and benefited with longer maintenance of 18 months in addition to oral etoposide for 21 days in each 28 days cycle. Gadner et al also described high mortality rate associated with MS-LCH with RO+.…”
Section: Discussionmentioning
confidence: 90%
“…The children who did not respond promptly to vinblastine and prednisolone had an unfavorable prognosis with survival rate of only 10-34%. The children with refractory LCH can be treated with allogeneic hematopoietic stem cell transplantation with guarded prognosis [14]. Some children experience reactivation after initial improvement; therefore, close follow-up with complete physical examination and growth monitoring is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of patients with neurodegeneration or with relapsed/refractory risk‐organ positive LCH remains challenging. Finally, having the goal of optimizing outcomes, is it possible to simplify complex treatments for LCH to make them accessible globally where financial and other resources might be limited (Narula et al , )?…”
Section: Discussionmentioning
confidence: 99%